CORAL REEF MANAGEMENT IN PADAIDO MARINE TOURISM PARK, BIAK NUMFOR Case Study for The Alternative Solution to Destructive Fishing Practices on Coral Reefs - Supriharyono . (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Coral reef is the most productive marine ecosystem in coastal waters. Unfortunately, this ecosystem has already suffered from non-sustainable human use including destructive fishing practices (bombing and cyanide), coral mining, over fishing, settlement pollution and uncontrolled tourism development. These affected the production of those fisheries resources in coral reefs. In order to manage those resources, such alternative to destructive use need to be studied. This paper reports alternative solution to destructive fishing practices  on coral reefs. The study has been carried out at Padaido Marine Tourism Park, the District of Biak Numfor, West Papua province, for about 2 weeks, 9-18 June 2001.  Survey method was used during the study.  The data were collected using Participatory Rapid Appraisal (PRA)’s method, with members of fisher group as the participants. Three kinds of reef fish groups are identified at the Padaido Islands waters, i.e. major group, target group, and indicator group. These include ornamental and consumption fishes.  Fish were caught with several fishing gears; while some of them are identified as destructive fishing practices, e.g. bomb, cyanide fishing. However, some of them can be recommended as sustainable fishing technologies, i.e. (1) squid jig, (2) troll line, and (3) hand line.